Resistance of F1 segregating populations derived from crosses between wild banana accessions Musa acuminata spp. burmannicoides Calcutta 4 and M. balbisiana Montpellier to black leaf streak disease - Vroh Bi, Irie; Zandjanakou-Tachin, Martine; Mbah, W.; Tenkouano, A.; Ojiambo, P.; Bandyopadhyay, Ranajit (International Society for Horticultural Science, 2009)
Banana ranks among the four most important crops in the developing world. A significant proportion of world production is also imported and consumed in developed nations. Mycosphaerella leaf spot diseases caused by Mycosphaerella species are major threats to banana production. Breeding for resistance is the most sustainable approach to controlling Mycosphaerella leaf spot diseases for which an understanding of the genetics of plant resistance and the genetic diversity of the pathogen is required. The most common Mycosphaerella leaf spot disease in Nigeria is black leaf streak caused by M. fijiensis. A Nigerian isolate of M. fijiensis was used to assess the resistance of segregating populations of selfed Musa acuminata ssp. burmannicoides (‘Calcutta 4’) and also M. acuminata spp. burmannicoides ‘Calcutta 4’ × M. balbisiana ‘Montpellier’. The results showed that resistance is quantitative. Using Punnett squares, the resistance in wild diploid species and the variable levels of susceptibility in major triploid cultivars, including dessert banana (AAA), plantain (AAB) and cooking banana (ABB), was simulated and explained. Finally, investigations on the identity of the ancestral parents of the AAB-genome plantain cultivars, AAA-genome East African highland banana cultivars and ABB-genome cooking banana cultivars are proposed for better resistance breeding